Advanced Functional Materials Proceedings of Chinese Materials Conference 2017 (Springer Singapore, 2018)
This proceedings volume gathers selected papers presented at the Chinese Materials Conference 2017 (CMC2017), held in Yinchuan City, Ningxia, China, on July 06-12, 2017. This book covers a wide range of metamaterials and multifunctional composites, multiferroic materials, amorphous and high-entropy alloys, advanced glass materials and devices, advanced optoelectronic and microelectronic materials, biomaterials, deformation behavior and flow units in metastable materials, advanced fibers and nano-composites, polymer materials, and nanoporous metal materials. The Chinese Materials Conference (CMC) is the most important serial conference of the Chinese Materials Research Society (C-MRS) and has been held each year since the early 1990s. The 2017 installment included 37 Symposia covering four fields: Advances in energy and environmental materials; High performance structural materials; Fundamental research on materials; and Advanced functional materials. More than 5500 participants attended the congress, and the organizers received more than 700 technical papers. Based on the recommendations of symposium organizers and after peer reviewing, 490 papers have been included in the present proceedings, which showcase the latest original research results in the field of materials, achieved by more than 300 research groups at various universities and research institutes.